2008
DOI: 10.1103/physrevb.77.125411
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of Pt monatomic chains

Abstract: The mechanical properties of Pt monatomic chains were investigated by a simultaneous measurement of effective stiffness and conductance using our recently developed mechanically controllable break junction technique with a tuning fork as a force sensor. When stretching a monatomic contact ͑two-atom chain͒, the stiffness and conductance increases at the early stage of stretching and then decreases just before breaking, which is attributed to a transition of the chain configuration and bond weakening. A statisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 25 publications
(58 reference statements)
3
41
0
Order By: Relevance
“…It was reported that the Young's modulus of Au ASWs is 47-116 GPa. 50 From the elongation length and corresponding farce increase in time f and g, we estimated the stiffness of the three-atom Pt ASW observed to be 5 Ϯ 1 N/ m. This value is at least six times larger than the stiffness of Pt ASWs with the same length ͑0.8 N/m͒, 37 whereas it is comparable with a stiffness of Au ASWs ͑5.8 N/m͒. 5 As shown in Fig.…”
Section: Figmentioning
confidence: 81%
See 2 more Smart Citations
“…It was reported that the Young's modulus of Au ASWs is 47-116 GPa. 50 From the elongation length and corresponding farce increase in time f and g, we estimated the stiffness of the three-atom Pt ASW observed to be 5 Ϯ 1 N/ m. This value is at least six times larger than the stiffness of Pt ASWs with the same length ͑0.8 N/m͒, 37 whereas it is comparable with a stiffness of Au ASWs ͑5.8 N/m͒. 5 As shown in Fig.…”
Section: Figmentioning
confidence: 81%
“…29,32,54,55 As previously reported, peaks are observed at 1.3-1.8G 0 in conductance histograms when pure Pt NCs are retracted in ultrahigh vacuum. 32,36,37 On the other hand, peaks near 0.2 and ϳ0.9G 0 are observed beside a trough near 0.5G 0 when Pt NCs are examined in a hydrogen atmosphere. 32,55 In accordance with these previous results, we classified the Pt ASWs observed in this study, since a hydrogen molecules is not imaged by HRTEM ͑Ref.…”
Section: Structure and Conductance Of Pure And Hydrogen-incorporatmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic chains are appealing systems for the study of a large variety of phenomena, including atomic scale magnetism [17][18][19] , nanoelectromechanics 20,21 , and quantum effects in one dimension [22][23][24][25] . Chains of atoms suspended between two electrodes are particularly interesting systems for the study of electronic transport due to their relative simplicity.…”
Section: Main Textmentioning
confidence: 99%
“…We start by examining the structural and conductance properties of atomic chains that are formed when a metallic wire with a narrow constriction is pulled apart. Experiments were performed on Au and Pt wires using a break junction setup 36 which the tensile forces in the chain amount to a degree where it either breaks or an additional atom is pulled into the chain 20,21 . The peak separation (2.6±0.2Å for Au and 2.0±0.2Å for Pt) indicates the average distance by which the chain is stretched before another atom is added to the chain 26 .…”
Section: Main Textmentioning
confidence: 99%